DEVELOPMENT OF A TRACKING TOOL FOR PEOPLE WITH ALZHEIMER’S - Vanessa Ruiz Diaz de Salvioni, Viviana; Armoa, Alcides; Javier Ibarra, Alexis (Journal of Interdisciplinary Debates, 2023)
This project consists of the creation of a mobile application, implemented on the Android platform that supports the daily activities of patients suffering from Alzheimer’s, the application will allow the real-time location of the patient to be sent, as well as an alert for the development of the mobile application App was used. In this investigation, a descriptive-explanatory analysis was carried out, which allowed us to interpret the events that have arisen, through a field investigation, directed to those in charge of people suffering from Alzheimer’s at the San Agustín nursing home, thus showing through of statistical data, the knowledge of the Managers, and an interview with the Mother Superior, for which the data collection was carried out with a sample population of 30 people. Through this research work, it has become clear that the implementation of the monitoring device is considered reliable and beneficial for the inmates of the San Agustín nursing home, based on the results given by the survey and the interview. At present, wireless technology provides many accessibility such as GPS receivers, which allows new applications to be made, allows measurements to be made in places where cables are not appropriate. To achieve this, it has been studied and analyzed how the GSM/GPRS/GPS technologies interact in the monitoring process. The model describes how the GPS receivers receive the signal from the satellites, calculate the position and through the GSM/GPRS network, the coordinates are transmitted to an App server so that the person who has a problem can be monitored. Alzheimer’s. According to the results obtained, the model is reliable because the correct measurement of the position of the person suffering from Alzheimer’s is obtained, guaranteeing their safety and tranquility of their family.